Microplastic pollution in Vembanad Lake, Kerala, India: The first report of microplastics in lake and estuarine sediments in India. (March 2017) - Sruthy, S.; Ramasamy, E.V.
Abstract: We present the first study of microplastics in the sediments of Vembanad Lake, a Ramsar site in India. Microplastics are emerging pollutants of increasing environmental concern with a particle size of <5 mm, which originate from successive degradation of larger plastic debris or are manufactured as small granules and used in many applications. The impact of microplastics pollution on the environment and biota is not well known. Vast data exist in the literature on marine microplastics while reports on freshwater ecosystems are scarce. In this context, to examine the occurrence of microplastic particles (MPs) in the Vembanad Lake, samples were collected from ten sites and processed for microplastic extraction through density separation. Identification of the polymer components of MPs was done using micro Raman spectroscopy. MPs were recovered from all sediment samples, indicating their extensive distribution in the lake. The abundance of MPs recorded from the sediment samples is in the range of 96–496 particles m −2 with a mean abundance of 252.80 ± 25.76 particles m −2 . Low density polyethylene has been identified as the dominant type of polymer component of the MPs. As clams and fishes are the major source of protein to the local population, the presence of MPs in the lake becomes critically important, posing a severe threat of contaminating the food web of this lake. This study, being the first report from India on MPs in lake sediments, provide impetus for further research on the distribution and impact of this emerging pollutant on the biota of many aquatic systems spread across India. Graphical abstract: Highlights: Microplastics were prevalent in all sediment samples of Vembanad Lake, India. Polyethylene is the dominant polymer type. Microplastics in sediments is a serious threat as the benthic dwelling clams are consumed by the local population. Abstract : Microplastics abundance is reported for the first time for sediments of Vembanad Lake, a Ramsar Site in India.